Trade and human development in OIC countries: a panel data analysis - Hamid, Zarinah; Mohd Amin, Ruzita (Islamic Research and Training Institute (IRTI), Islamic Development Bank, 2013)
This study examines the relationship between trade and the OIC countries 19 social developments as measured by the Human Development Index (HDI) using the generalized method of moments (GMM) procedure in a panel data distributed lag model for the years 1980 to 2005, with a five-year increments as well as annual data from 2000 to 2009. It addresses two questions: (i) whether trade has a positive relationship with human development as reflected by longevity, educational attainment and income in the HDI measurement, and (ii) whether trade still has a positive relationship with human development, when the income component of the HDI is excluded. Comparisons are made across OIC countries based on three World Bank Classifications by Income, namely, high income, middle income and low income countries. Trade is found to have a significant positive relationship with HDI for all income categories, but insignificant relationship with non-income HDI. The finding indicates that trade is associated with human development only through income channels, and it is not associated with other components, such as longevity, literacy level and educational attainment. More of appropriate and effective public policies need to be formulated and implemented so as to achieve the desired outcomes of multi-dimensional human development in the true sense of the word.